2009
DOI: 10.1007/s11771-009-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BaO addition on relative density and electric conductivity of xNi/10NiO-NiFe2O4 cermets

Abstract: xNi/10NiO-NiFe 2 O 4 (x=5, 10, 17) cermets and those doped with 1% BaO (mass fraction) were prepared by cold isostatic pressing at 200 MPa and sintering in nitrogen atmosphere at 1 473 K. The effects of BaO addition on relative density, microstructure and electric conductivity of cermets were investigated. The results show that relative densities of xNi/10NiO-NiFe 2 O 4 cermets (x=5, 10, 17) doped with 1% BaO at 1 473 K in nitrogen atmosphere are increased by 0.49%, 1.45% and 2.99% compared with those of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Indeed, according to the results, the relative densities improved from 91.75% in C0 to 93.44%, 94.90%, and 95.63% in CB1, CB3, and CB5 specimens, respectively. Han-Bing et al achieved a similar density increment trend during the addition of 1 wt% of BaO into 5Ni/10NiO.NiFe 2 O 4 , cermets [22]. It is proposed that the densification process is due to the mass transfer of vacancies which are related to Fe and O elements.…”
Section: Microstructure and Relative Densitymentioning
confidence: 85%
See 1 more Smart Citation
“…Indeed, according to the results, the relative densities improved from 91.75% in C0 to 93.44%, 94.90%, and 95.63% in CB1, CB3, and CB5 specimens, respectively. Han-Bing et al achieved a similar density increment trend during the addition of 1 wt% of BaO into 5Ni/10NiO.NiFe 2 O 4 , cermets [22]. It is proposed that the densification process is due to the mass transfer of vacancies which are related to Fe and O elements.…”
Section: Microstructure and Relative Densitymentioning
confidence: 85%
“…In this research, in order to ascend the chemical reaction of particles and therefore achieving reasonable results, it is supposed to use FeSO for further investigation on this issue [3,[19][20][21]. Therefore, the present work principally concentrates on the effect of additive BaCO 3 as a possible modifier of structure [22] on the mechanical properties of 5Ni/10NiO.90NiFe 2 O 4 cermet. In order to obtain the composition, a specific amount of each raw material (FeSO 4 .6H 2 O and NiSO 4 .6H 2 O) with regards to the stoichiometric calculations were mixed for 24 h using jar-mill process, in which the ratio of alumina balls to powder was 2:3, and methanol was selected as a dispersant.…”
Section: Introductionmentioning
confidence: 99%
“…Xi Jinhui,et al [7][8][9][10]. investigated that TiO 2 , MnO 2, and V 2 O 5 were doped , and found that the density, bending strength and electrical conductivity of NiFe 2 O 4 cermet doped is better than the sample undoped HE Hanbing,et al [11] studied the effect of the xNi/10NiO-NiFe 2 O 4 (x=5, 10,17)doped BaO on electrical conductivity and found that when doping amount of BaO is 1%, its electrical conductivity at 1273K were 21.98 S/cm, 28.37 S/cm and 50.10 S/cm, respectively, but the conductivity of sample undoped were 18.70, 22.79 and 39.58 S / cm, respectively. Meer, et al [12] showed that CaO added is advantageous to the densification of Mg-Zn ferrite.…”
Section: Introductionmentioning
confidence: 99%